Changes in Dentists' Prescribing Patterns in Norway 2005-2015 - Reidun Lisbet Skeide Kjome; Joachim André Johansen Bjønnes; Henning Lygre (Elsevier, 2022)
Background: There is scant knowledge of dentists' total prescribing patterns, and little is published on this internationally. The Norwegian Prescription Database (NorPD) includes data on all dispensed prescription medication in Norway from 2004 and can be used to investigate how dentists' prescribing has changed over time. There are few Norwegian guidelines supporting dentists' prescribing, and Norwegian legislation on dentists' prescribing rights leaves room for interpretation. The aim of this study was therefore to give an overview of all prescribing from dentists in Norway in the period 2005 to 2015 and to identify trends in their prescribing pattern over this time span. We also give characteristics of the prescribing dentists. Methods: The study had a retrospective pharmacoepidemiologic design. Data on all medication prescribed by dentists and dispensed from Norwegian pharmacies in the time period 2005 to 2015 were extracted from the NorPD. Changes over time in the prescribers, patients, and medications are reported. Results: There was an increase of 50% in total number of prescriptions from dentists in Norway from 2005 to 2015; adjusted for the growth in population, there was a 33% increase. The majority of prescriptions from dentists were for antibiotics and analgesics; however, the data reveal that the dentists prescribed from all major therapeutic groups. Dentists increased antibiotic prescribing in a period when total antibiotic prescribing in Norway decreased. Conclusions: Our study finds antibiotics and analgesics dominate prescriptions from Norwegian dentists and shows an increase in use over time. It highlights the need for creating evidence-based prescribing guidelines for dentists and for ensuring that existing guidelines are implemented.